Molecular typing of dengue virus in Mizoram, Northeast India - Sailo, Christine Vanlalbiakdiki; Ghatak, Souvik; Sarathbabu, Subbarayan; Bariha, Girija Shankar; Majumder, Ayan; Singh, Abhinav; Lalremruata, Ralte; Zomawia, Eric; Lalrinpuia, Benjamin; Lalfak zuali; Zothanzama, John; Senthil Kumar, Nachimuthu (The Journal of Infection in Developing Countries, 2022)
Introduction: Dengue is an emerging vector-borne public health threat and characterization at the molecular level is important for proper management of the disease. The aim of the study is to examine the diversity of the dengue viral serotypes from a hilly mountainous region of Northeast India. Methodology: Thirty-six blood samples that were positive for dengue virus IgM antibodies identified by the enzyme-linked immunosorbent assay (ELISA) method were collected and quantified for the IL6 gene expression by using reverse transcriptase polymerase chain reaction (RT-PCR). Results: All the patients had dengue hemorrhagic fever (DHF); 12 samples had a monotypic infection and 14 samples had dual infection with various dengue virus (DENV) serotypes; one sample had triple infection with DENV-1, DENV-2, and DENV-3. Conclusions: This study identified DENV-1 as the major serotype in the state of Mizoram and it is the first report on the molecular typing of the dengue virus from the hilly mountainous state located in the Indo-Burma region bordering Myanmar and Bangladesh.